Le site des Cougnets (Hérault) : un habitat pastoral des xiie et xiiie siècles au cœur des conflits entre monastère et communautés villageoises - Charlotte Britton (Archéologie Médiévale)
This study is the first step of an archaeological study of scattered Medieval settlements in Mediterranean scrublands. The site of Les Cougnets, a small hamlet of dry stone walled huts associated with a pastoral enclosure, represents a grouping of independent units, used in either a temporary or cyclical manner during the second half of the twelfth and the thirteenth centuries. Indeed, dominating the Hérault valley and located a few hundred metres from the Aniane monastery, this area is in the heartland of the Benedictine abbey domain, to which large amounts of pastoral land were adjoined during the Middle Ages. Finally, written records shed light upon feuds between the Abbey and local populations brought about by ecclesiastical seizure of pastures and woods, throughout the Middle Ages and right up to the Revolution.